2021
DOI: 10.2196/preprints.30766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

User Experience, Engagement, and Popularity in Mental Health Apps: Secondary Analysis of App Analytics and Expert App Reviews (Preprint)

Abstract: BACKGROUND User experience and engagement are critical to mental health apps’ abilities to support users. However, limited work has examined the relationship between user experience, engagement, and app popularity. Given that apps vary immensely in their popularity, understanding why some mental health apps are more appealing or engaging to users can inform efforts to develop better apps. OBJECTIVE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This suggests that when mental health apps are well-designed and user-friendly, they can be powerful tools for mental health support 67 . It has also been shown that poor usability can lead to reduced user satisfaction, decreased engagement, and increased abandonment rates in mental health apps 55,56 . These findings underscore the importance of ensuring excellent usability in such technology and highlight the need to focus on user engagement in mental health apps, emphasizing the need for robust measurement, reporting, and validity assessment in the development of effective mental health apps 55 .…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that when mental health apps are well-designed and user-friendly, they can be powerful tools for mental health support 67 . It has also been shown that poor usability can lead to reduced user satisfaction, decreased engagement, and increased abandonment rates in mental health apps 55,56 . These findings underscore the importance of ensuring excellent usability in such technology and highlight the need to focus on user engagement in mental health apps, emphasizing the need for robust measurement, reporting, and validity assessment in the development of effective mental health apps 55 .…”
Section: Related Workmentioning
confidence: 99%
“…Engagement with mental health apps is influenced by several factors, including content, user experience, and the degree of usercenteredness. This is particularly evident where engagement is crucial for the effectiveness of the intervention [55][56][57][58] . The significance of usability is multifaceted.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that when mental health apps are well-designed and user-friendly, they can be powerful tools for mental health support 68 . It has also been shown that poor usability can lead to reduced user satisfaction, decreased engagement, and increased abandonment rates in mental health apps 56,57 . These findings underscore the importance of ensuring excellent usability in such technology and highlight the need to focus on user engagement in mental health apps, emphasizing the need for robust measurement, reporting, and validity assessment in the development of effective mental health apps 56 .…”
Section: Related Workmentioning
confidence: 99%
“…Engagement with mental health apps is influenced by several factors, including content, user experience, and the degree of usercenteredness. This is particularly evident where engagement is crucial for the effectiveness of the intervention [56][57][58][59] . The significance of usability is multifaceted.…”
Section: Introductionmentioning
confidence: 99%